2015
DOI: 10.1128/jvi.03144-14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Angiopoietin-1 Upregulation in Kaposi's Sarcoma-Associated Herpesvirus-Infected PEL Cell Lines

Abstract: Angiopoietin-1 (ANGPT-1) is a secreted glycoprotein that was first characterized as a ligand of the Tie2 receptor. In a previous study using microarray analysis, we found that the expression of ANGPT-1 was upregulated in Kaposi's sarcoma-associated herpesvirus (KSHV)-infected primary effusion lymphoma (PEL) cell lines compared with that in uninfected Burkitt and other leukemia cell lines. Other authors have also reported focal expression of ANGPT-1 mRNA in biopsy specimens of Kaposi's sarcoma (KS) tissue from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Ang-1 is ubiquitously expressed in endothelial cells, whereas Ang-2 has been found to be upregulated at the sites of vascular remodeling [ 25 , 100 , 102 , 103 ]. Recently, a study from Keiji Ueda’s group reported that DNA binding factors, including octamer-binding transcription factor (OCT1), play a key role in the upregulation of ANGPT-1 transcriptional activity in PEL cells [ 104 ], further indicating that cellular micro environments created by KSHV infection are most probably due to the upregulation of ANGPT-1 expression and may directly contribute to the disease progression in AIDS patients with PEL [ 104 ].…”
Section: Kshv-mediated Angiogenesismentioning
confidence: 99%
“…Ang-1 is ubiquitously expressed in endothelial cells, whereas Ang-2 has been found to be upregulated at the sites of vascular remodeling [ 25 , 100 , 102 , 103 ]. Recently, a study from Keiji Ueda’s group reported that DNA binding factors, including octamer-binding transcription factor (OCT1), play a key role in the upregulation of ANGPT-1 transcriptional activity in PEL cells [ 104 ], further indicating that cellular micro environments created by KSHV infection are most probably due to the upregulation of ANGPT-1 expression and may directly contribute to the disease progression in AIDS patients with PEL [ 104 ].…”
Section: Kshv-mediated Angiogenesismentioning
confidence: 99%
“…As archived in most literature, Angpts are usually expressed by pericytes and secreted to the extracellular matrix (ECM), whereby contributing to neovascularization in the TME niches. However, recent studies revealed that Angpt1 is upregulated in Kaposi's sarcomaassociated herpesvirus (KSHV)-infected primary effusion lymphoma (PEL) cell lines, with the expression level higher than that in uninfected lymphoma or leukemia cell lines [47]. The reason is, some KSHVinfected PEL cell line-specific DNA-interacting factors, such as Oct 1, binds to the Angpt1 promoter region (-143 to -125) thereby regulating its expression.…”
Section: Pathological Sources Of Angpt1 and Angpt2 In The Tme Under Gmentioning
confidence: 99%